The political U - Campos, Nauro,Coricelli, Fabrizio,Frigerio, Marco (IZA - Institute of Labor Economics, 2022)
This paper throws new light on the relationship between income and democracy. Using data for 162 countries over 1960-2018, we show that the causal relationship between political and economic development is U-shaped:
10419/265819
Keywords: Graue Literatur; democracy; income; growth; political development; economic development; non-linearity